OʻZBEKISTON IQTISODIYOTIGA TOʻGʻRIDAN-TOʻGʻRI XORIJIY INVESTITSIYALAR OQIMINI OSHIRISHNING SAMARALI STRATEGIK YOʻNALISHLARI (Marketing Journal, 2026)
AbstractThis article provides a scientific analysis of effective strategic directions forincreasing the inflow of foreign direct investment (FDI) into the economy ofUzbekistan. Based on the transformation of global investment flows, processes oftechnological modernization, and the national economic development strategy, theinstitutional, sectoral, and regional mechanisms for attracting FDI are examined. Anintegrated strategic model is proposed on the basis of statistical data and currentinvestment programs.Keywords: foreign direct investment, investment climate, industrialtransformation, global value chain, export diversification, free economic zones, ESG,technology transfer.